Novel Methotrexate-Ciprofloxacin Loaded Alginate-Clay Based Nanocomposite as Anticancer and Antibacterial Co-Drug Delivery System - Mehrdad Mahkam; Fatemeh Bazmi Zeynabad; Effat Alizadeh; Mahdi Rahimi; Fariborz Rahimi; Roya Salehi (Tabriz University of Medical Sciences, 2021)
Purpose: In last decades, by increasing multi-drug resistant microbial pathogens an urgent demand was felt in the development of novel antimicrobial agents. Methods: Promising nanocomposites composed of clay/alginate/imidazolium-based ionic liquid, have been developed via intercalation of calcium alginate and ionic liquid by ion exchange method. These tailored nanocomposites were used as nanocarriers to simultaneously deliver methotrexate (MTX), and ciprofloxacin (CIP), as anticancer and antibacterial agents, respectively to MCF-7 breast cancer cells. Nanocomposites were fully characterized by scanning electron microscopy studies (SEM), X-ray diffraction (XRD), Fourier transforms infrared (FTIR) spectroscopy, and thermogravimetric analysis (TGA) methods. The in vitro antimicrobial potential of the mentioned nanocomposites in free and dual-drug loaded form was investigated on Pseudomonas aeruginosa and Escherichia coli bacteria. The antitumor activity of nano-formulations was evaluated by both MTT assay and cell cycle arrest. Results: The dual drug-loaded nanocomposites with exceptionally high loading efficiency (MTX: 99 ±0.4% and CIP: 98 ±1.2%) and mean particle size of 70 nm were obtained with obvious pH-responsive MTX and CIP release (both drugs release rate was increased at pH 5.8 compared to 7.4). The antibacterial activity of CIP-loaded nanocomposites was significantly higher in comparison with free CIP (P<0.001). The antitumor activity results revealed that MTX cytotoxicity on MCF-7 cells was significantly higher in nano-formulations compared to free MTX (P<0.001). Both MTX-loaded nanocomposites caused S-phase arrest in MCF-7 cells compared to non-treated cells (P˂ 0.001). Conclusion: Newly developed smart nanocomposites are potentially effective pH-sustainable delivery systems for enhanced tumor therapy.